Pemberdayaan Kader Posyandu dalam Pencegahan Stunting pada Masa Pandemi Covid-19 di Banjar Baturiti Tengah, Desa Baturiti, Kerambitan, Tabanan - Asri Lestarini; Ni Wayan Rusni (UNHI Press, 2022)
The prevalence of stunting in Tabanan Regency, Bali Province in 2018 was 16.2%. One of the villages from Tabanan Regency that has stunting cases is Baturiti village, and one of the toddlers is from Banjar Baturiti Tengah. The risk factors for stunting found in the Banjar Baturiti Tengah community are the lack of knowledge, attitudes and behavior regarding good parenting for children and the difficulty of Posyandu cadres to carry out Posyandu activities for Toddlers due to the COVID-19 pandemic. These are the basis for counseling and assistance to Posyandu cadres in Banjar Baturiti Tengah regarding good parenting for children and providing health support equipment so that it supports Posyandu activities and can prevent stunting. The counseling activities will be carried out at the Banjar Baturiti Tengah Hall by involving about 6 participants who are cadres of Posyandu of the Banjar Baturiti Tengah. The result of this program is an increase in knowledge of posyandu cadres as indicated by an increase in posttest results (average 95) compared to pretest (mean 61.67). Posyandu cadres' skills appear to have improved from the results of observations in providing stunting prevention so that education can build community behavior in preventing stunting.